Service Quality, Company Image, Trust and Its Influence On Customers’ Satisfaction and Loyalty at Bank Shariah Mandiri (BSM) Meulaboh Branch Office - Sari, Nilam (Jurnal Ilmiah Peuradeun, 2018)
Global competition between conventional and shariah banks and the demands of providing maximum services to the customers and by looking at the rapid growth of Shariah Bank, it makes inter-institutional competition become significant. This cause’s shariah banking business is required to constantly improve the quality of its services. Customer satisfaction and loyalty in banking services is an important element in growing the company. It takes a special strategy to win the competition. This study aims to analyze the influence of service quality variables (service quality), corporate image (corporate image), and trust (trust) on customer satisfaction and loyalty. The analysis of data is using path analysis method and it takes 61 samples of the customers in PT. Bank Shariah Mandiri (BSM), Meulaboh. The sampling technique is simple random sampling. The results showed that the quality of service (service quality) has a positive and insignificant effect on customer satisfaction. Corporate image (corporate image) has a positive but not significant impact on customers’ satisfaction BSM. Trust (trust) has a positive and significant impact on customer satisfaction. BSM customers’ satisfaction has a direct effect on customers’ loyalty. Quality of service (service quality) has a positive and significant impact on customers’ loyalty. Corporate image (corporate image) positively and significantly affect the loyalty of BSM customers. Trust has negative and insignificant effect on customers’ satisfaction. By providing the results of this study, BSM is expected to always improve service quality, corporate image and customers’ trust, in which the three elements are very important and decisive in growing the company to continue to exist to deal with the global competition.